Genetic characterization of juvenile sudden cardiac arrest and death in Tuscany: The ToRSADE registry - Girolami, Francesca; Spinelli, Valentina; Maurizi, Niccolò; Focardi, Martina; Nesi, Gabriella; Maio, Vincenza; Grifoni, Rossella; Albora, Giuseppe; Bertaccini, Bruno; Targetti, Mattia; Coppini, Raffaele; Favilli, Silvia; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Sudden cardiac arrest (SCA) in young people represents a dramatic event, often leading to severe neurologic outcomes or sudden cardiac death (SCD), and is frequently caused by genetic heart diseases. In this study, we report the results of the Tuscany registry of sudden cardiac death (ToRSADE) registry, aimed at monitoring the incidence and investigating the genetic basis of SCA and SCD occurring in subjects < 50 years of age in Tuscany, Italy. Methods and results Creation of the ToRSADE registry allowed implementation of a repository for clinical, molecular and genetic data. For 22 patients, in whom a genetic substrate was documented or suspected, blood samples could be analyzed; 14 were collected at autopsy and 8 from resuscitated patients after SCA. Next generation sequencing (NGS) analysis revealed likely pathogenetic (LP) variants associated with cardiomyopathy (CM) or channelopathy in four patients (19%), while 17 (81%) carried variants of uncertain significance in relevant genes (VUS). In only one patient NGS confirmed the diagnosis obtained during autopsy: the p.(Asn480Lysfs*20) PKP2 mutation in a patient with arrhythmogenic cardiomyopathy (AC). Conclusion Systematic genetic screening allowed identification of LP variants in 19% of consecutive patients with SCA/SCD, including subjects carrying variants associated with hypertrophic cardiomyopathy (HCM) or AC who had SCA/SCD in the absence of structural cardiomyopathy phenotype. Genetic analysis combined with clinical information in survived patients and post-mortem evaluation represent an essential multi-disciplinary approach to manage juvenile SCD and SCA, key to providing appropriate medical and genetic assistance to families, and advancing knowledge on the basis of arrhythmogenic mechanisms in inherited cardiomyopathies and channelopathies.